How to Improve the Effect of Microvascular Decompression for Hemifacial Spasm: A Retrospective Study of 32 Cases with Unsuccessful First Time MVD - Xia, Yun-fei; Zhou, Wei-ping; Zhang, Ying; Li, Yan-zhen; Wang, Xu-hui; Li, Shi-ting; Zhao, Hua (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background Microvascular decompression (MVD) has become accepted as an effective therapeutic option for hemifacial spasm (HFS); however, the curative rate of MVD for HFS varies widely (50–98%) in different medical centers. This study could contribute to the improvement of the MVD procedure.Methods We retrospectively analyzed 32 patients in whom initial MVD failed in other hospitals and who underwent a second MVD at our center. The clinical characteristics, operative findings, outcome of the second MVD, and complications were recorded.Results There were 18 women and 14 men (56.3 and 43.7%, respectively). The left-to-right ratio was 19:13. The mean age of the patients was 59.8 years. We found an undiscovered conflict site located in zone 4 in 10 patients and in the root entry zone in 8 patients. The initial MVD failed in nine patients because of ignorance of the arterioles that originate from the anterior inferior cerebellar artery. There were no special findings in four patients. No Teflon felts were found in the whole surgical field in one patient.Conclusion Omission of the offending vessel is the most common cause of an unsuccessful MVD. Intraoperative abnormal muscle response associated with the Z-L response is a good measure to correctly identify the involved arterioles.
Keywords: microvascular decompression; hemifacial spasm; offending vessels; reoperation